Improving alumni administration by self-built information system : building IMMIT connected' to enhance alumni connection - Li, Yixiang (My University, 2011)
Alumni are considered as precious resource of the institutions, thus improving alumni adminis-tration is critical. In information era, alumni administration is assisted by widespread information technology, such as social network sites. This paper aims to discover if a self-built information sys-tem would enhance alumni connection in the IMMIT context, and what kind of attributes would be helpful applying to the special context. The current online alumni services at other universities and at the IMMIT host university are analyzed, and then social media is introduced. After illustrating the social capital existing in IM-MIT, the type of the self-built information system is suggested, following an interpretation of the prototype. Two research models are utilized in this article: TAM and intentional social action model. The second model is adjusted with proposed parameters. Afterwards, a survey and an interview protocol are designed under the guidance of the models. The results are analyzed in several groups, and the proposed parameters are tested. A conclusion is drawn to indicate how to improve alumni‟s intention to use and how to achieve a better-accepted design.